UbiComp 2006: Ubiquitous Computing 8th International Conference, UbiComp 2006, Orange County, CA, USA, September 17-21, 2006, Proceedings - Dourish, Paul.; Dourish, Paul.; Friday, Adrian.; Friday, Adrian. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2006)
Fifteen years after the publication of Weiser’s seminal paper in Scientific American, ubiquitous computing is a large, thriving field of academic research and commercial innovation. The proceedings of the 8th International Conference on Ubiquitous C- puting reflect the strength, diversity and vigor of the research program that Weiser initiated. We hope that you will find much in the papers contained herein to stimulate new and exciting work as we reach forward toward ubiquitous computing together. The location of the conference, in Orange County, California, was particularly - posite given recent directions in the field. A Pacific Rim location linked the conf- ence to last year’s venue in Tokyo, Japan, and provided an appropriate space to reflect on the different implementations and visions of ubiquitous computing in d- ferent parts of the world. Two significant elements of local industry – the software industry and the entertainment industry – reflect concerns heavily represented in - cent research in ubiquitous computing, with mobile and ubiquitous gaming, for - stance, an obvious link. The unique metropolitan setting of the Los Angeles region provided a useful setting in which to develop research agendas in urban computing. Finally, while there are no papers in the proceedings on surfing-based Ubicomp, the cultural focus on healthy lifestyles in Southern California relates to concerns with aging and health as important application areas for ubiquitous computing technologies and solutions.